Application of neuroeducational strategies as perceived by educational specialists - Valladolid De la Cruz, Diana Elizet (2023)
Currently, teaching methodologies are oriented to the development of competencies in students. However, multiple international evaluations show gaps in teaching practices. Specifically, in the area of pedagogical strategies, which hinder the development of meaningful learning in students. In view of this problem, the question arose: What are the perceptions of educational specialists on the integration of neuroeducational strategies in the pedagogical process at the secondary level? This was the starting point for this research. The general objective of this research was to analyze the perceptions of educational specialists on the integration of neuroeducational strategies in the pedagogical process at the secondary level. For an adequate investigative processing, we worked with a qualitative approach framed in the naturalistic paradigm and a phenomenological design. The instrument used to collect the perceptions of the specialists was an interview guide. As a result, it was concluded that educational specialists are aware of the contribution of the neuroeducational field. However, they do not have the necessary knowledge to apply the strategies in the classroom. Therefore, it was recommended that teachers interested in improving their pedagogical work be trained and/or updated with scientific knowledge about brain functioning.